Comparison of linear and non-linear earthquake response of masonry walls - Sayin, Erkut; Calayir, Yusuf (Techno-Press, 2015)
In this study, linear and non-linear response of a masonry wall that includes an opening was presented. The masonry wall was modeled with two-dimensional finite elements. Smeared crack model that includes the strain softening behavior was selected to the masonry wall material. For the numerical application, linear and non-linear analyses of the masonry wall were carried out using east-west and vertical components of the 1992 Erzincan and 2003 Bingol earthquake acceleration records. Linear and non-linear solutions were compared each other. The displacement and stress results at the selected points of the masonry wall and crack propagation in the masonry wall were presented for both earthquake acceleration records.
Keywords: masonry wall; non-linear analysis; smeared crack model